Factors Associated with Utilisation of Sexual and Reproductive Health Services Among Undergraduates of University Of Ilorin, Nigeria (MUST JOURNAL OF RESEARCH AND DEVELOPMENT, 2025)
The utilization of reproductive health services is crucial for preventing health issues such as sexually transmitted infections and enhancing fertility and overall quality of life. However, among undergraduates, the utilization of these services is not well documented, and several factors may influence their use. The objectives of the study were to determine whether accessibility; affordability; knowledge of reproductive health; and quality of service are factors associated with utilisation of sexual and reproductive health services among Undergraduates of University of Ilorin, Nigeria. A descriptive survey research design was adopted for the study. The population comprised all 46,657 undergraduates of University of Ilorin, Nigeria. Four hundred and eleven (411) respondents were sampled. A multistage sampling procedure was adopted for the study. A researcher-structured questionnaire validated by three experts from the department was used for data collection. The reliability of the instrument was established through split-half method and a co-efficient of 0.86r was obtained using Cronbach Alpha. Inferential statistics of chi-square was used to test the hypotheses at 0.05 alpha level. The findings of the study were that accessibility (ᵪ2 = 183.38), affordability (ᵪ2 =125.92); knowledge of reproductive health (ᵪ2 =103.55); quality of service (ᵪ2 = 115.25) are factors associated with utilisation of sexual and reproductive health services among Undergraduates of University of Ilorin, Nigeria. The study recommended that these factors should be improved to enable undergraduates to optimally utilise sexual and reproductive health services.